Instrumentos de gestión y su influencia en la gestión de la calidad educativa en las instituciones educativas del nivel secundario jornada escolar regular Requena 2023 - Gaviria Rios, James William (Universidad Nacional de la Amazonía Peruana, 2025)
The general objective of this study is to explain the influence of management instruments on the management of educational quality in secondary level educational institutions with regular school hours in the city of Requena-2023. An explanatory research methodology was used with field, bivariate and cross sectional designs. The sample is made up of 96 teachers and directors from 4 secondary education institutions with regular school hours (JER), who were administered a survey composed of two questionnaires previously validated through item, construct and reliability analysis by experts. The results of the statistical analysis indicate that the correlation is inverse but not statistically significant p-value > 5% significance. The results of the statistical analysis indicate that the correlation is inverse but not statistically significant p-value > 5% significance. According to the results, it is concluded that (there is no significant association) it is not pertinent to determine the model of educational quality management in secondary level educational institutions with regular school hours in the city of Requena-2023.

Este estudio tiene como objetivo general explicar la influencia de los instrumentos de gestión en la gestión de la calidad educativa en las instituciones educativas del nivel secundario con jornada escolar regular de la ciudad de Requena-2023. Se utilizó una metodología de investigación tipo explicativa con diseños de campo, bivariado y transversal. El grupo de estudio está compuesto por 96 profesores y directivos de cuatro escuelas de educación secundaria con jornada escolar regular (JER)., a quienes se administró una encuesta compuesta por dos cuestionarios previamente validados mediante análisis de ítems, constructo y confiabilidad por expertos. Los resultados de análisis estadístico indican que la correlación es inversa pero estadísticamente no es significativa p-valor > 5% de significancia. Según los resultados se concluye que (no existe asociación significativa) no es pertinente determinar el modelo de la gestión de la calidad educativa en las instituciones educativas del nivel secundario con jornada escolar regular de la ciudad de Requena-2023.
Keywords: Instrumentos de gestión; Gestión de la calidad educativa; Alumnos; https://purl.org/pe-repo/ocde/ford#5.03.01